Psychological Factors of Youth Emigration Intentions: A Review of International Studies - Nadezhda V. Murashcenkova (Peoples' Friendship University of Russia (RUDN University), 2021)
The psychological factors of the emigration intentions of young people, the growth of which is observed today in various countries of the world, are analysed based on the data of numerous international studies. The scientific significance of this analysis, on the one hand, is due to the lack of Russian psychological works that systematize and popularize the relevant information, on the other hand, it is associated with the need to subsequently correlate the results of international and Russian studies in order to identify common supra-cultural and specific psychological factors that affect the emigration intentions of young people. The psychological driving forces of the emigration intentions of young people considered in international studies are diverse and correspond to different levels of personality activity (individual, interpersonal and macrosocial). They correlate with general groups of factors contributing to emigration. The factors reflecting the emerging opportunities for emigration are related to positive attitudes towards emigration in general, the consideration of emigration as a way to achieve significant goals, a low degree of attachment to the country of origin, dissatisfaction with the existing living conditions, and positive attitudes towards the country where young people intend to move to. The psychological factors associated with the availability of social support include the support they receive from their families as well as relevant interpersonal contacts they have abroad. The group of factors related to personal resources for overcoming emerging obstacles correlates with expressed career aspirations, high motivation for power and achievements, insignificant motivation for affiliation, extraversion, openness to new experience, desire for risk, change and new impressions, openness to the world and cultural differences, readiness to interaction with others, faith in other religions and nationalities, self-efficacy, ability to cope with the ambivalence of emerging emotions and feelings, a high level of education, proficiency in foreign languages, and experience of international mobility. The obtained data can be used to conduct empirical psychological studies on the driving forces of the emigration activity of young people in Russia and other countries.